Assistência estudantil na UFMA, dinâmica institucional e significados na formação: evidências da modalidade vivências acadêmico-profissionais - SILVA, Allana Sousa (2020)
The study has as its theme the student assistance policy for higher education, highlighting its meaning in academic formation and institutional dynamics. The Programa Nacional de Assistência Estudantil (PNAES) was part of the reform of higher education in the Lula Government aimed at the permanence of the student, primarily those with a per capita family income of up to one and a half wages. This research aims to analyze the process of implementing academic-professional experiences and their meanings for the training of students at the Universidade Federal do Maranhão (UFMA). The research has a qualitative approach, bibliographic studies, document analysis and descriptive-analytical research are carried out, using semi-structured interviews. Theoretical basis is: Sposati; Zago; Lima; Demo; Vasconcelos; Pinto; Kowalski and others. Also, the main Official Documents related to the theme are valued, such as Normative nº 39/2007 and Decree nº 7.234/2010. The analyzes indicate that the student assistance actions developed at UFMA are instituted through public notices, considering that the guiding document of the institutional policy is being restructured by the specific collegiate body; some areas defined by the PNAES are not being developed in the Pró-Reitoria de Assistência Estudantil (Proaes), but are being developed by action of other sectors of UFMA, highlighting the need for partnerships between institutional sectors. Furthermore, it is clear that both in the national Program and in the institutional notices, the orientation that the scholar-professional actions of the fellow is related to his training project prevails. However, the statements of the professionals in the sectors interviewed indicate that the perspective of student assistance has an assistentialist tendency, based on the counterpart and technical-administrative activities. Proaes professionals see the stock exchange as a right, but highlight some challenges in its implementation. The scholarship holders mainly highlight the financial support of the Exchange and the contribution with regard to interpersonal relationships and professional posture. Thus, the study suggests expanding the discussion with the academic community about the scholarship proposal and its relationship between the student's course of origin and activities developed to expand the training process.